Reducing Cyberbullying in Schools International Evidence-Based Best Practices - Campbell, Marilyn; Campbell, Marilyn (Elsevier Science, 2018)
Reducing Cyberbullying in Schools: International Evidence-Based Best Practices provides an accessible blend of academic rigor and practical application for mental health professionals, school administrators and educators, giving them a vital tool in stemming the problem of cyberbullying in school settings. It features a variety of international, evidence-based programs that can be practically implemented into any school setting. In addition, the book looks at a broad array of strategies, such as what can be learned from traditional bullying programs, technological solutions, policy and legal solutions, and more.Provides overviews of international, evidence-based programs to prevent cyberbullying in schoolsPresents an academically rigorous examination that is also practical and accessibleIncludes technological and legal strategies to stem cyberbullying in schoolsLooks at the prevalence and consequences of cyberbullying